Effects of Urtica dioica dichloromethane extract on cell apoptosis and related gene expression in human breast cancer cell line (MDA-MB-468) - Mohammadi, A; Mansoori, B; Goldar, S; Shanehbandi, D; khaze, V; Mohammadnejad, L; Baghbani, E; Baradaran, B (Cellular and Molecular Biology, 2016)
Breast cancer is the most common cancer among women in worldwide, especially in developing countries. Therefore, a large number of anticancer agents with herbal origins have been reported against this deadly disease. This study is the first to examine the cytotoxic and apoptotic effects of Urtica dioica in MDA-MB-468, human breast adenocarcinoma cells. The 3-(4,5-dimethylethiazol-2 yl)-2,5- diphenyltetrazolium (MTT) reduction and trypan-blue exclusion assay were performed in MDA-MB-468 cells as well as control cell line L929 to analyze the cytotoxic activity of the dichloromethane extract. In addition, Apoptosis induction of Urtica dioica on the MDA-MB-468 cells was assessed using TUNEL (terminal deoxy transferase (TdT)-mediated dUTP nick- end labeling) assay and DNA fragmentation analysis and real-time polymerase chain reaction (PCR). The results showed that the extract significantly inhibited cell growth and viability without inducing damage to normal control cells. Nuclei Staining in TUNEL and DNA fragments in DNA fragmentation assay and increase in the mRNA expression levels of caspase-3, caspase-9, decrease in the bcl2 and no significant change in the caspase-8 mRNA expression level, showed that the induction of apoptosis was the main mechanism of cell death that induce by Urtica dioica extract. Our results suggest that urtica dioica dichloromethane extract may contain potential bioactive compound(s) for the treatment of breast adenocarcinoma.